2020
DOI: 10.1111/odi.13532
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 oral‐associated lesions: Discussion of elicited response

Abstract: This pandemic phenomenon has generated a large number of publications (May 19 in PubMed 2,267), all of them aimed a better knowledge of its microbiological and serological characteristics, clinical expressions, and complications, trying to find those situations that could be more serious indicators. The search for these characteristics does not escape the oral sphere. Our group had the opportunity to find the cases presented, and the only thing we tried to do was to shed some light on the fact that oral lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“… 12–14 However, it is still controversial whether these symptoms/signs are specific to COVID-19 disease as a result of the SARS-CoV-2 infection or as a result of other underlying conditions and consequences, such as co-infections, immune system impairment caused by the virus, or adverse effects of COVID-19 medications. 15 …”
Section: Introductionmentioning
confidence: 99%
“… 12–14 However, it is still controversial whether these symptoms/signs are specific to COVID-19 disease as a result of the SARS-CoV-2 infection or as a result of other underlying conditions and consequences, such as co-infections, immune system impairment caused by the virus, or adverse effects of COVID-19 medications. 15 …”
Section: Introductionmentioning
confidence: 99%
“…We are seeing different hypotheses that have been raised to explain the interaction between the virus and periodontitis, including the approaches taken by Martín Carreras-Presas et al, (2020) and Patel and Woolley (2020). However, because this viral agent is so new, there are no clinical or population studies with greater power of scientific evidence to prove this association.…”
Section: E T T E R T O T H E E D I T O Rmentioning
confidence: 99%
“…Furthermore, the oral cavity has a crucial role in the dissemination of SARS-CoV-2 virus since it serves as a gateway to the internal environment of the human body. It has been suggested that oral manifestations associated with COVID-19 may be either related to the direct efect of the SARS-CoV-2 on the tissues of the oral cavity or an indirect efect due to an impairment of the immune system by the virus [6,7]. Oral manifestations related to COVID-19 infection have important negative impacts on nutrition, quality of life, and the psychological status of patients.…”
Section: Introductionmentioning
confidence: 99%